microRNAs en envejecimiento cardiaco humano: dianas terapéuticas y biomarcadores - Hernández Bellido, Natalia; Ramos Marquès, Estel; Hernández Vicente, Adrián; García Mendivil, Laura; Santander Badules, Hazel; Mercanti, Giada; Garrido Huéscar, Elisa; Garatachea, Nuria; Köhler, Ralf; Pueyo, Esther; Ordovás, Laura (Jornada de Jóvenes Investigadores del I3A, 2023)
Cardiovascular diseases (CVD) are the leading cause of death globally, being age one of the most important predisposing risk factor. MicroRNAs (miRNAs) are key post-transcriptional regulators of multiple biological processes, including cardiac aging. MiRNAs are nowadays emerging therapeutics. Also, miRNAs are cutting-edge biomarkers, as they can be actively or passively released from tissues to body fluids (i.e. blood) acting as indicators of physiological and pathophysiological processes in tissues. However, the role of miRNAs in age-related cardiac remodelling is poorly understood in humans. This limits their use as anti-aging interventions, to reduce the risk of CVD, but also as biomarkers of the true physiological state of the heart in relation to age (biological age indicators). Our group recently described the miRNome dynamics with age, chronological and biological, of the human left ventricle. We identified a number of miRNAs related to biological age (BIO-AGEmiRNAs) and bioinformatically established their downstream gene regulation network. Also, a number of cardiac-enriched BIO-AGEmiRNAs were described. Here, we aim to validate the BIO-AGEmiRNA regulatory network and to describe miRNA indicators of the biological age of the heart.